PENGARUH DISIPLIN DAN MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI IPS SMAN 1 BUKIT BATU KABUPATEN BENGKALIS - Melly Miranda; Almasdi Syahza; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the influence of discipline and learning interest of students towards learning achievement of economic subjects students of class XI IPS SMAN 1 Bukit Batu Bengkalis. This study population is students of class XI IPS that have smester Final Examination (UAS) even below the minimum value Conditions Criteria (KKM) of 39 students. The method used was a questionnaire and documentation. Methods of data analysis in this research using descriptive analysis and multiple regression analysis. Based on the research results obtained information that X positive and significant effect on Y. Results R Square shows by 0,550 this means that the variables affecting the discipline and interest in learning achievement variable learn by 55%. Thus it can be said that the capability and interest in learning discipline variables affect achievement variable learn is strong.Key Words: Discipline Learnig, Interest Learning, Learning Achievement .